Construction of college student’s volleyball functional physical training system based on 5G embedded analysis from the perspective of biomechanics - Shang, Xiaoxia; Zhao, Jinliang; Gu, Cuifeng (Molecular & Cellular Biomechanics, 2024)
In volleyball, the movement and performance of athletes are closely related to biomechanical principles. The process of getting the ball beyond the opponent’s net and landing on the court involves complex biomechanical actions such as jumping, spiking, and blocking. These actions require appropriate muscle activation, joint movement, and force generation. Through a 5G embedded physical training system, college students’ biomechanical performance in volleyball can be effectively monitored and analyzed. For example, the Wireless Sensor Network (WSN) can be used to measure the forces exerted on the body during movements, such as the impact force on the fingers during spiking and blocking, and the stress on the lower back. By analyzing these biomechanical data, problems such as finger injuries and lower back pain can be better understood and addressed. Moreover, the 5G embedded system allows for a detailed analysis of the biomechanical characteristics of different teams and players, enabling coaches and athletes to optimize training strategies. The system can also provide visual feedback on biomechanical parameters, which helps students improve their overall coordination and muscle strength. By incorporating biomechanical analysis into the volleyball physical training system, students can better understand the scientific basis of their movements and improve their performance. Statistical analysis has been carried out effectively based on the study analysis with the existing open-source datasets, providing a quantitative basis for biomechanical research and training optimization.